CONSTRUCTION OF ADAB EDUCATION INPUT THROUGH HIDDEN CURRICULUM AT ISLAMIC BOARDING SCHOOL, SOUTH SUMATRA - Ali, Mukti; Sirozi, M; Munir, Munir (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The challenge of modernization in Islamic boarding schools involves balancing the formal religious curriculum with practical skills and daily life lessons. Purpose: This study explores the role of the hidden curriculum in the construction of adab (manners) education at the Qodratullah Banyuasin Islamic Boarding School in South Sumatra, Indonesia. Adab education, integral to Islamic character formation, extends beyond formal learning and is deeply embedded in the social interactions, daily activities, and institutional culture of Islamic boarding schools. Method: Utilizing a case study approach, this research employs interviews, observations, and documentation as data collection methods. Result: The findings indicate that the hidden curriculum significantly contributes to the development of adab through three primary inputs: figure-based education, literacy, and activities. Figure-based education, exemplified by the role of the kyai (Islamic scholar), establishes a model for students in terms of behavior, values, and norms. Literacy-based education fosters critical thinking and intellectual growth through the study of Islamic texts. Activity-based education emphasizes social interactions and extracurricular activities that reinforce communal values and ethics. Conclusion: This research highlights the importance of the hidden curriculum in shaping students' character, demonstrating how adab education in Islamic boarding schools provides a holistic framework for character and moral development, combining both formal and informal educational processes. The study offers valuable insights for educational policymakers seeking to integrate Islamic values into the educational system while addressing the challenges of modernization and globalization.